“Semua Aku Dirayakan” in the Lyrics of Nadin Amizah’s Song - Tri Yanti Monika; Fahrul Rozi; Siti Khumayah; Aghnia Dian Lestari (CV. Media Digital Publikasi Indonesia, 2025)
Music has a significant role as a universal communication tool that is able to express feelings, ideas, emotions and reflections to its listeners. The song